Oral production in language learning: an analysis of teachers’ feedback used to correct iv semester students oral mistakes (2018)
In the past years, The Modern Languages Program has researched about feedback strategies only for correcting written essays, so as to improve writing skills in the reading and writing subject. The previous research was made by Garcia and Rico (2015), and it was called Metacognition as a Way to Improve L2 Writing. This research project was worthy for the professors who are using this tool to give feedback to the students in order to make them realize about their own mistakes. On the other hand, it is important to understand that writing is not the only subject or skill the program should focus on. Oral production is a key subject for the development of a second language. Under those circumstances, as a high quality program, it needs to supply strategies to every language skill in order to fulfill students’ learning needs. In that sense, it is important to search about the different feedback strategies provided by the professors of the program in order to correct their students’ oral production.